THE EFFECT OF ADMINISTRATION OF ETHANOL EXTRACT FROM MUSA PARADISIACA L. (MPL) FRUIT ON THE CASPASE-3 MRNA GENE EXPRESSION IN RAT AMYLOID BETA INDUCED, AN ALZHEIMER'S DISEASE MODEL - Kamelia, Emma; Asadul Islam, Andi; Hatta, Mochammad; Kaelan, Cahyono; Patellongi, Ilhamjaya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study is to analyze caspase-3 mRNA gene expression in a Wistar rat model of Alzheimer's disease (AD) treated with Musa paradisiaca L. (MPL) ethanol extract or banana extract (BE) Methods: MPL was evaluated for its effect on the caspase-3 mRNA gene expression of rat amyloid beta (AÎ²) induced, an AD model. Each model included twenty Wistar rats were randomized into five groups: K0, without AD induction and no BE; K1, AD induction and no BE; K2, AD induction+BE 250 mg/kg body weight (BW); K3, AD induction+BE 500 mg/kg; and K4, AD induction+BE 1000 mg/kg. AD induction was performed by AÎ²1-42 (0.2 ug) injection at the intracerebroventricular area. mRNA caspase-3 level measurements were performed by real time-polymerase chain reaction. Results: Paired t-test analysis showed no significant differences of caspase-3 mRNA level before AÎ² induction among five groups (p>0.05). At 6 weeks post-AÎ² induction, there was significantly increased caspase-3 mRNA in all groups except K0 (p<0.05). Notably, after 3 weeks of BE administration, caspase-3 mRNA expression was significantly decreased in all BE-treated groups; in the K1 placebo group, caspase-3 mRNA expression increased. The maximum decreased caspase-3 mRNA expression was in group K4 (-BE 1000 mg/kg BW), and the minimum was in group K2 (-BE 250 mg/kg BW). Conclusion: The results revealed that the ethanolic extract of MPL fruit could decrease caspase-3 mRNA gene expression in AD rat.